Necesidad de establecer las causales para la terminación de la unión de hecho en el Código Civil Ecuatoriano - Jaramillo Vivanco, Marìa Eugenia (2015)
This paper gives a brief overview of the legal principles established in the Constitution of the Republic of Ecuador, the Civil Code, Code of Civil Procedure regarding Ecuadorian Dissolution of Marriage Legislation in the Ecuadorian Society; is why in the development of this research has analyzed all that has to do with the de facto union: its history, constitutional development, the requirements for their existence and all that encompasses the legal treatment of company assets. The theme chosen for this thesis states: "NEED FOR THE GROUNDS FOR TERMINATION OF THE UNION MADE IN ECUADOR CIVIL CODE"; the same were raised objective "Making a legal, critical and doctrinal study of law marriage and its termination in the Ecuadorian civil law". Similarly, the hypothesis states: "Allow the dissolution of the union made unilaterally violates the rights of the abandoned spouse". To get to check each of these expressions , I conducted a literature which was the basis for the field research itself in the opinion of lawyers of those who obtained it was established in conclusion that the present procedure to provide for finished violent union rights made one spouse , causing serious damage socially and economically. It is established so that research framed in a deep doctrinal legal analysis has validity and reliability criteria lawyers professionals with vast experience provided me, to finally present the conclusions, recommendations and legal reform of the Civil Code, I propose as an alternative solution to this problem